A neotype for Homunculus patagonicus Ameghino, 1891, and a new interpretation of the taxon - Tejedor, Marcelo Fabian (2008)
Homunculus patagonicus was first described by Ameghino in 1891. A few studies have since added to the literature but our understanding of the affinities of this late early Miocene species or its role in the evolutionary history of Patagonian primates and the platyrrhines as a whole has remained quite limited. This is partly due to the loss of the type specimen. Here we designate a neotype, MACN-A 5757, the best preserved mandible from the original Ameghino collection of primates of Santacrucian Land Mammal Age that was likely discovered in the same general area as Ameghino’s type. Our reanalysis of the available craniodental material of Homunculus patagonicus, mostly from this series, indicates that its morphology strongly resembles that of modern pitheciines and their fossil relatives but tends to be more primitive. Like these other forms, Homunculus presents a derived incisor-canine complex, with a compact incisor battery, at least moderately high crowned but narrow incisors, and possibly a large, robust canine. The incisors are probably semi-procumbent, arrayed in front of the canines, and the mandible is probably relatively narrow anteriorly, a combination of features that parallels some of the advanced callitrichines, Callithrix and Cebuella. The mandibular profile is remarkably similar to Aotus, including the extinct A. dindensis from younger deposits of La Venta, Colombia. The partial cranium from the original series is notable for its flat frontal trigon, wide interorbital region, unenlarged orbits, deep maxilla and large maxillary sinus, and proclivous premaxilla. Long bones preserve limb proportions similar to modern quadrupedal platyrrhines, such as Aotus and Callicebus, which lack advanced leaping adaptations. Other Patagonian fossil pitheciines are discussed and compared, along with the additional records of this subfamily outside Argentina. Overall, Homunculus appears to have been a primitive pitheciine, with versatile adaptations resembling the quadrupedal, diurnal titi monkeys, including an emphasis on feeding on tough fruits.